Monitoring ionospheric scintillations with GNSS in South America - Vani, Bruno César (2021)
At equatorial latitudes, during specific conditions, Global Navigation Satellite System (GNSS) signals traversing the ionospheric layer might experience fluctuations in phase and/or amplitude, the so-called ionospheric scintillations. This chapter presents a discussion about the scope, achieved results, and prominent challenges imposed by ionospheric scintillations in South America. The discussions are supported by data from different networks of Ionospheric Scintillation Monitor Receivers deployed in the South American region. Results presented here include aspects of the climatology of scintillations in this region, describing the dynamics of equatorial plasma bubbles driving scintillation as observed in the applied GNSS monitoring data. Effects of scintillations on GNSS observables and positioning are also demonstrated with an experimental setup on field application. Characteristics of the statistical modeling of amplitude scintillations and the importance of different statistical parameters are presented and discussed. Description and results of a low-cost instrumentation for monitoring scintillations are also presented, highlighting its effectiveness and potentials for future research and applications.